Unexpected large evasion fluxes of carbon dioxide from turbulent streams draining the world’s mountains - Åsa Horgby (Nature Portfolio, 2019)
Freshwater systems are important components of the carbon cycle, but the extent of their role in CO2 fluxes is poorly understood. Here Horgby and colleagues show that mountain streams are a surprisingly large source of CO2 to the atmosphere, with annual emissions that belie their spatial extent.